PENGEMBANGAN PTERIDISC POKOK BAHASAN PTERIDOPHYTA SEBAGAI MEDIA PEMBELAJARAN TAKSONOMI TUMBUHAN - Anna nurlia; Bambang Hariyadi; muswita muswita (BIODIK, 2015)
Standards learning competency plant taxonomy is, students can understand and explain the principles of classification, description, identification, nomenclature, and knowing the morphological and anatomical structure of plants. Students can achieve competence learning if the student successfully mastered the material plant taxonomy. The absence of appropriate learning media to optimize students' understanding of the taxonomy of plant material can cause difficulties or obstacles for students to understand the material plant taxonomy. Therefore, the development of instructional media in the form of Pteridisc needs to be done. The purpose of this study was to determine the end product of learning media Pteridisc on the subject of Pteridophyta and to determine the response students of Biology Education PMIPA FKIP University ofÂ  jambi to use as a learning medium Pteridisc plant taxonomy. Based on the results obtained validation, assessment for each indicator on the design aspects of the media were on both criteria with the average percentage of 75%, and ratings for the indicators on the material aspects of the media are on the criterion of good and very good, with a mean percentage of 86, 7%. Student responses to assessment of each indicator in the trial against the use of a small group of media currently on the criteria very well with the average of the responses given percentage 94.23%, and student responses to assessment of each indicator in a large group trials are in very good criteria with the average percentage of 87.82%. It can be concluded that the instructional media products Pteridisc subject Pteridophyta included in the criteria very well, so it can be used by the student in learning activities. Â  Keywords: development, instructional media, taxonomy Pteridophyta